Replication of a Rank-Framed Social Norms Experiment. Issue 3 (27th May 2018) - Pariera, Katrina L.
Abstract : Decades of research on the social norms approach (SNA) has shown that informing people of how their behavior compares to their peers is an effective way to reduce risky behavior. The SNA has been particularly successful at reducing drinking on college campuses. However, one recent study may have found a way to improve upon the SNA: rank-framing messages. This study found that reframing social norms messages to show how students' alcohol consumption ranks relative to their peers is more effective at increasing information seeking. The current study is a replication of this study. Rank-framed messages did decrease drinking behaviors but did not increase information seeking. Possible explanations and the potential merit of rank-framed social norms interventions are discussed.